Following Cu Microstructure Evolution in CuZnO/Al2O3(−Cs) Catalysts During Activation in H2 using in situ XRD and XRD‐CT. Issue 1 (3rd August 2022) - Farmer, Daniela M.; Jacques, Simon D. M.; Waller, David; Boullosa Eiras, Sara; Roy, Kanak; Held, Georg; Sankar, Gopinathan; Beale, Andrew M.
Abstract: Understanding how the microstructure of the active Cu 0 component in the commercially applicable Cu/ZnO/Al2 O3 (−Cs2 O) low‐temperature water‐gas shift catalyst evolves under various H2 partial pressures in the presence/absence of a Cs promoter during thermal activation has been investigated. Time‐resolved XRD and spatially‐resolved XRD‐CT data were measured as a function of H2 concentration along a packed bed reactor to elucidate the importance of the zincite support and the effect of the promoter on Cu sintering mechanisms, dislocation character and stacking fault probability. The rate of Cu reduction showed a dependency on [Cs], [H2 ] and bed height; lower [Cs] and higher [H2 ] led to a greater rate of metallic copper nanoparticle formation. A deeper analysis of the XRD line profiles allowed for determining a greater edge character to the dislocations and subsequent stacking fault probability was also observed to depend on higher [H2 ], smaller Cu 0 (and ZnO) crystallite sizes, increased [ZnO] (30 wt.%, sCZA) and lower temperature. The intrinsic activity of Cu/ZnO/Al2 O3 methanol synthesis catalysts has been intimately linked to the anisotropic behaviour of copper, and thus the presence of lattice defects; to the best knowledge of the authors, this study is the first instance in which this type of analysis has been applied to LT‐WGS catalysts. Abstract : Detailed analysis of XRD data reveals insight into the metallic Cu microstructure in industrial‐like Cu/ZnO/Al2O3 low temperature water‐gas shift (LT‐WGS) catalysts as a function of linear and radial distribution in a packed‐bed reactor. The presence of Cs in the formulation is revealed to affect the stacking faulting in Cu.